TSSC: a new deep learning model for accurate pea leaf disease identification - Xu, Laixiang; Chang, Yibu; Li, Chenyang; Zhang, Yang; Yang, Xiaodong; Chen, Xinjia; Cai, Zhaopeng; Zhao, Junmin (Frontiers in Plant Science, 2025)
ProblemAccurate diagnosis of plant diseases is crucial for ensuring crop yield and food safety. This study aims to explore a deep learning based intelligent recognition methods for plant leaf diseases to solve the automatic recognition problem of various pea leaf diseases.MethodologyWe propose a novel deep learning framework called TSSC. First, a three-neighbor channel attention is designed to promote the effectiveness of feature extraction. Second, a complementary squeeze and excitation mechanism is introduced to enhance the ability to extract key features. Finally, a split attention module is embedded to reduce model complexity.ResultsThe experimental results demonstrate that the proposed model achieves an overall classification accuracy of 99.61% and outperforms other excellent deep learning models.ContributionThe currently proposed system provides an effective solution for image recognition of complex plant diseases and has reference value for the development of mobile disease detection equipment.